2021
DOI: 10.15252/emmm.202114035
|View full text |Cite
|
Sign up to set email alerts
|

The respiratory syncytial virus (RSV) prefusion F‐protein functional antibody repertoire in adult healthy donors

Abstract: Respiratory syncytial virus (RSV) is the leading cause of death from lower respiratory tract infection in infants and children, and is responsible for considerable morbidity and mortality in older adults. Vaccines for pregnant women and elderly which are in phase III clinical studies target people with pre-existing natural immunity against RSV. To investigate the background immunity which will be impacted by vaccination, we single cell-sorted human memory B cells and dissected functional and genetic features o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 54 publications
0
17
1
Order By: Relevance
“…Preliminary exploratory data revealed that the V-306 study subjects displayed higher titer changes in PCA assays when the pre-fusion F protein conformation of RSV F was used as the capturing antigen (unpublished data), likely reflecting a better accessibility of the relevant epitope on the pre-fusion F protein. This may also reflect the diversity of pre-existing neutralizing and non-neutralizing antibodies [ 29 ], and their capacity to interfere with the binding of anti-FsIIm epitope-specific IgG to the PVZ-binding epitope [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary exploratory data revealed that the V-306 study subjects displayed higher titer changes in PCA assays when the pre-fusion F protein conformation of RSV F was used as the capturing antigen (unpublished data), likely reflecting a better accessibility of the relevant epitope on the pre-fusion F protein. This may also reflect the diversity of pre-existing neutralizing and non-neutralizing antibodies [ 29 ], and their capacity to interfere with the binding of anti-FsIIm epitope-specific IgG to the PVZ-binding epitope [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The data show that, while three subjects had generated antibodies specific for the pre-fusion form of the F protein, the majority of neutralizing antibodies were directed against the F protein bound to both the pre- and post-fusion forms. However, 78 of the 82 antibodies with dual-binding capacity were bound significantly more strongly to the pre-fusion form, which is found most predominantly on virus particles [ 47 ]. The data from these studies emphasize that the neutralization of virus infectivity in vivo is a potentially complex combination of a spectrum of different antibodies with different neutralizing activities.…”
Section: What Can the Sars-cov-2 Field Learn From The Respiratory Syn...mentioning
confidence: 99%
“…Multiple antigenic sites have been identified on both RSV F and hMPV F proteins. Among the six known antigenic sites of RSV F, pre-fusion-specific sites Ø and V are targeted by over 60% of neutralizing antibodies in humans ( 26 , 27 ), indicating these sites are vital for immune recognition and antibody neutralization ( 28 ). hMPV F shares three antigenic sites (III, IV, V) with RSV F, as several antibodies have been found to cross-react with RSV and hMPV F at these epitopes ( 29 32 ).…”
Section: Introductionmentioning
confidence: 99%